Предмет: Алгебра,
автор: gavrini
Ответы
Автор ответа:
0
(2x+3)/(x-2)^2-(x-1)/x(x-2)-5/x=0
(2x+3)*x-(x-1)(x-2)-5(x-2)^2=0 x<>0 x<>2
2x^2+3x-x^2-2+3x-5x^2-20+20x=0
3x-2+3x-20+20x=0
-4x^2+26x-22=0
2x^2-13x+11=0
x1=11/2
x2=1
(2x+3)*x-(x-1)(x-2)-5(x-2)^2=0 x<>0 x<>2
2x^2+3x-x^2-2+3x-5x^2-20+20x=0
3x-2+3x-20+20x=0
-4x^2+26x-22=0
2x^2-13x+11=0
x1=11/2
x2=1
Автор ответа:
0
=============================================
Приложения:
![](https://files.topotvet.com/i/834/834c812299b459f287132b45aa5b3ced.jpg)
![](https://files.topotvet.com/i/4b8/4b8c3e948542b54a8ed345e95c71d8c6.jpg)
Похожие вопросы
Предмет: Физика,
автор: garripotter8633
Предмет: Математика,
автор: stanislavaborisova08
Предмет: Литература,
автор: mn2qw1123
Предмет: Биология,
автор: иринааааааааааааааа
Предмет: Математика,
автор: Максоня